National Character Education in Teaching Balinese for Grade Seven of SMP Negeri 1 Singaraja - I Kadek Mustika (LP2M STIT Palapa Nusantara, 2016)
The study is aimed at describing the national character education in (1) planning, (2) implementation, and (3) evaluation of the implementation of the Balinese instruction in VIII grade of SMA Negeri 1 Singaraja. The subjects in this research were the Balinese language teachers in class VIII A1 and VIII A2. The objects of research were : (1) the national character education in the instruction planning of learning, (2) the national character education in the implementation of learning, and (3) the national character education in the evaluation of the implementation. There were three research methods, namely the recording of documents to collect planning of learning data, observation to collect implementation data and evaluation of the implementation, and interviews to support planning, implementation, and evaluation of the implementation data. The data were analyzed by using data analysis techniques model of Miles and Huberman, namely data reduction, data presentation, and inference and verification. The conclusion of this study showed that (1) the national character education in the planning of learning has been implemented by teachers with conformity percentage of 81% (very appropriate). The planned score was fourteen, which lied in the components of learning objectives, learning activities, and assessment. (2) The national character education in the implementation of learning has been implemented in three main activities of learning with conformity percentage of 72% (appropriate). There were fourteen values which were implemented, but they were not fully comply with the planning and implementation guidelines. The instructional methods used in the character formation were exemplary, verbal reinforcement, motivation, instruction and assignments. (3) The national character education in the evaluation of the implementation has been implemented in conformity percentage of 85% (very appropriate). Teachers assessed the attitude / character, knowledge, and skills. There were five evaluated character values, which referred from the indicator and standard score developed at school. The techniques used in this study were observation and assessment which were conducted in the form of process and product assessment. Thus, we can conclude the national character education in Balinese instuction has been implemented by the teacher. The suggestion that can be given in this research is that the teachers should be more careful in planning particular components of the assessment. Moreover, Buleleng Education Office should improve the provision of training in implementing the national character education.